Dental Erosions: A Manifest of Gastroesophageal Reflux Disease (GERD) - Mohsin Masud, Salman Azhar, Ali Raza, Madiha Rasheed, Ammara Riaz, Afham Shahid (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To record the frequency of dental erosion (DE) in patients with Gastro esophageal Reflux Disease (GERD). Methodology: The research included a total of one hundred patients who had been diagnosed with gastro esophageal reflux disease. Duration of study was 3 months from July, 2022 to September, 2022. Patients who presented with a digestive system illness in which stomach acid splashed over the bottom of the esophagus met the criteria for a diagnosis of GERD, which we utilized to make the diagnosis. It manifested itself in the form of a strong burning feeling in the chest, which often occurred after meals and typically occurred many times each week. Endoscopy and the patients’ medical histories were used to make the diagnosis. For the purpose of making a tooth erosion diagnosis, GERD patients were evaluated presenting in the Madinah teaching hospital Faisalabad. It was shown that individuals who suffered from GERD had a significantly higher incidence of tooth erosion. Results: In our study, 46(46%) cases were between 30-45 years of age while 54(n=54) were between 46-60 years of age, mean age was calculated as 46.14+11.85 years. Gender distribution shows that 51(51%) were male while 49(49%) were females. DE was recorded in 34(34%) while 66(66%) had no findings of the morbidity; we found no significant difference in age and gender. Conclusion: Patients with gastroesophageal reflux disease often have dental erosion as a presenting symptom (GERD). Screening individuals with GERD for tooth erosion is crucial for identifying and treating instances timely to enhance patients’ quality of life. Keywords: Gastro esophageal Reflux Disease (GERD), Adults, Dental Erosion (DE)